Amyloidosis in Inflammatory Bowel Disease: A Systematic Review of Epidemiology, Clinical Features, and Treatment - Joan Toscá; Marta Maia Boscá-Watts; Rosario Antón Ausejo; Sandra Tejedor Alonso; Francisco Mora Miguel; Miguel Mínguez (2016)
Amyloidosis is a rare complication of inflammatory bowel disease [IBD]; its low prevalence has hindered both descriptive and therapeutic studies. The aim of this study was to estimate the prevalence of amyloidosis in IBD and the risk factors associated with this complication. This paper presents an observational study, followed by a systematic review of the epidemiological and clinical characteristics of the disease and a review of the diagnostic and therapeutic options. The prevalence of amyloidosis among IBD patients is 0.53% (95% confidence interval [CI]: 0.32–0.75), although epidemiological data suggest that it may be under-diagnosed. The phenotype most frequently associated with amyloidosis is males with aggressive and extensive Crohn's disease, fistulising behaviour, perianal disease, and extra-intestinal complications, with the development of proteinuria and renal failure. Identifying risk factors of amyloidosis in IBD patients and screening for proteinuric renal dysfunction are useful to improve diagnostic accuracy. Referral of biopsies to a tertiary centre should also be considered, to improve diagnostic accuracy. Although there is no reliable evidence on the effectiveness of treatment, it seems reasonable to treat the underlying disease with potent immunosuppression to minimise inflammatory activity, thereby switching off amyloidogenesis.